Challenges for Industrial Product/Service Systems: Experiences from a learning network of large companies - Sundin, E.; Ölundh Sandström, G.; Lindahl, M.; Öhrwall Rönnbäck, A.; Sakao, T.; Larsson, T. C. (Cranfield University Press, 2009)
In Sweden, there are a growing number of manufacturers that are using the approach of industrial product/service systems. This paper explores how manufacturers and university researchers have started a workshop series where important and topical product/service system issues are elucidated. The companies face many challenges in order to achieve a good product/service system business. Many challenges are related to changing different peoples’ mindset within the company and/or with external companies and customers. Having a learning network approach of dealing with these challenges has been perceived as a good manner of tackling the questions raised within the product/service system providing companies.
Organised by: Cranfield University
Keywords: PSS; Integrated Product Service Engineering (IPSE); IPS²; Learning networks